Three-Dimensional Numerical Analysis on Performance Enhancement of Micropolar Hybrid Nanofluid in Comparison with Simple Nanofluid. Issue 18 (11th October 2021) - Manaa, Nessrin; Abidi, Awatef; Saleel C., Ahamed; Madiouli, Jamel; Borjini, Mohammed Naceur
Abstract: The objectives of the present research work are the three-dimensional computational analysis and predictions on double-diffusive natural convection in a cubic cavity filled with Cu–Al2 O3 /water micropolar hybrid nanofluid. The governing equations are carefully modified employing vorticity–vector potential formulation and are solved by the finite volume method. Performance enhancement of Cu–Al2 O3 /water micropolar hybrid nanofluid is judiciously compared with the Cu/water simple nanofluid. Besides, the influences of concentration of nanoparticles, Rayleigh number, buoyancy ratio, and micropolar vortex parameter on the flow field and heat transfer are critically analyzed. The results show that heat and mass transfer rates are lower for a micropolar nanofluid model when compared to the pure nanofluid model. The hybrid micropolar nanofluid displays more heat and mass transfer rates for thermal buoyancy-dominated zones when compared with traditional nanofluid. Conversely, the heat and mass transfer rates are decreased when using micropolar hybrid nanofluid for the solutal-dominated regime. The enhancement of micropolar viscosity parameter results in a decrease of average Nusselt and Sherwood numbers which are more perceptible in the thermal buoyancy-dominated flow.